Conquered Populations in Early Islam : Non-Arabs, Slaves and the Sons of Slave Mothers - Urban, Elizabeth (Edinburgh Studies in Classical Islamic History and Culture, 2022)
Explores the ways in which new Muslims of slave origins were integrated into early Islamic societyChoice Outstanding Academic Title, 2020Brings together three separate groups (freedmen, slave women and the children of enslaved mothers) as parts of the same prism of unfreedomRecovers enslaved women's voices and treats them as important agents of historical changeCombines close textual analysis with large-scale demographic study to provide multiple levels of understandingExplores the transformation of Islam from a small piety movement to an imperial doctrine upholding the distinction between conquerors and conqueredChallenges simplistic notions of ethnicity and shows the categories of 'Arab' and 'non-Arab' are historically contingentThis book traces the journey of new Muslims as they joined the early Islamic community and articulated their identities within it. It focuses on Muslims of slave origins, who belonged to the society in which they lived but whose background of slavery rendered them somehow alien. How did these Muslims at the crossroads of insider and outsider find their place in early Islamic society? How did Islamic society itself change to accommodate these new members? By analysing how these liminal Muslims resolved the tension between belonging and otherness, Conquered Populations in Early Islam reveals the shifting boundaries of the early Islamic community and celebrates the dynamism of Islamic history.